Mindfulness Practice Is Associated With Subjective Wellbeing Homeostasis Resilience in People With Crohn's Disease but Not Ulcerative Colitis - Lyall, Kimina; Beswick, Lauren; Evans, Subhadra; Cummins, Robert A.; Mikocka-Walus, Antonina (Frontiers in Psychiatry, 2022)
Objectives: People with Crohn’s disease and ulcerative colitis (inflammatory bowel disease: IBD), commonly experience high levels of depressive symptoms and stress and low levels of subjective wellbeing (SWB). Mindfulness is increasingly considered an adjuvant IBD treatment. The relationships between depression, disease symptoms and mindfulness have not previously been considered within the theory of SWB homeostasis. This theory states that SWB is normally maintained by a homeostatic system around a setpoint range but can fail when psychological challenges dominate consciousness. This study explored the relationship among SWB and patient-reported psychological and IBD symptoms and investigated whether mindfulness practice is independently associated with SWB homeostatic resilience. Design: This cross-sectional study recruited participants through online IBD support groups. Methods: Participants (n = 739; 62% Crohn’s disease) detailed symptoms of depression and stress, patient-reported disease symptoms, and regularity of mindfulness practice. Results: The sample had significantly lower SWB (hedges g = -0.98) than normative data. A logistic regression found mindfulness practice doubled the Crohn’s disease participants’ odds of reporting SWB within the normal homeostatic range, after controlling for psychological, physical, and demographic variables (OR 2.15, 95% CI: 1.27, 3.66). A one-point increase of patient-reported bowel symptoms reduced the participant’s odds of reporting SWB in the normal homeostatic range by about a third (OR 0.66, 95% CI: 0.50, 0.85]). However, the influence of mindfulness or disease symptoms on SWB was not observed for people with ulcerative colitis. Conclusion: These findings provide initial evidence for an association between mindfulness and SWB homeostatic resilience in a clinical population.